Pediococcus pentosaceus PR-1 modulates high-fat-died-induced alterations in gut microbiota, inflammation, and lipid metabolism in zebrafish - Liu, Yue; Zhu, Danxu; Liu, Jiwen; Sun, Xiaoxia; Gao, Feng; Duan, Huiping; Dong, Lina; Wang, Xin; Wu, Changxin (Frontiers in Nutrition, 2023)
Obesity is a health issue worldwide. This study aimed to evaluate the beneficial effects of Pediococcus pentococcus PR-1 on the modulating of gut microbiota, inflammation and lipid metabolism in high-fat-diet (HFD)-fed zebrafish. Adult zebrafish were fed a commercial (C), high fat (H, 25% fat), probiotic (P, 106 CFU/g), or high fat with probiotic (HP) diets twice daily for 5 weeks. P. pentosaceus PR-1 reduced body weight and BMI, indicating its anti-obesity effect. The 16S rRNA sequencing results showed HFD induced a distinct gut microbiota structure from C group, which was restored by probiotic. P. pentosaceus PR-1 improved gut health by decreasing the abundance of Ralstonia and Aeromonas which were increased induced by HFD. Moreover, probiotic restored abundance of Fusobacteria, Cetobacterium and Plesiomonas, which were decreased in HFD-fed zebrafish. The results of quantitative real-time polymerase chain reaction showed probiotic suppressed HFD-induced inflammation by decreasing the expressions of IL-1β and IL-6. Levels of hepatic TNF-α, IL-1ß, and IL-6 were reduced by probiotic in HFD-fed zebrafish. Probiotic also ameliorated gut barrier function by increasing the expressions of occludin, Claudin-1 and ZO-1. Probiotic exerted anti-adipogenic activity through regulating the expressions of SREBP1, FAS and LEPTIN. Levels of hepatic triglyceride, total cholesterol, low density lipoprotein were also reduced by probiotic. Histological analysis showed probiotic alleviated liver steatosis and injury induced by HFD. P. pentosaceus PR-1 might be useful as a dietary health supplement, especially for reducing obesity.